Tindak Tutur Performatif dan Dimensi Psikologis Karakter dalam Novel Cantik Itu Luka karya Eka Kurniawan: Pendekatan Psikopragmatik - Amazeli, Renzy Agathy; Rafli, Zainal; Murtadoo, Fathiaty (Lingua Susastra, 2024)
This study investigates the speech acts and psychological dimensions of characters in Cantik Itu Luka by Eka Kurniawan through a psychopragmatic approach. Focusing on how speech acts reveal psychological states, the research examines expressions of trauma, inner conflict, social injustice, and emotional resilience in the novel. Utilizing a qualitative method with a case study design, the study selects significant dialogues and categorizes them into expressive, commissive, and representative acts to explore how language reflects the psychological experiences of each character. Results indicate that expressive speech acts unveil deep-seated emotions tied to past traumas, while commissive acts highlight social bonds and commitments, revealing the character’s coping strategies and emotional resilience. Through psychopragmatics, the analysis illustrates that language in literature serves not only as a communication tool but as a mirror to the characters' mental conditions, thereby enriching the narrative with complex psychological dimensions. This research contributes to literary and linguistic studies by demonstrating how language functions as an expression of inner life, opening pathways for future psychopragmatic explorations in literature.